LIESST Effect in Fe(II) 1,2,4-Triazole Chains - Garcia, Yann; Renz, Franz; Gutlich, Philipp (Current Inorganic Chemistry (Discontinued), 2016)
One-dimensional Fe(II) chains with 1,2,4-triazole as bridging ligands present the LIESST effect; i.e. their spin state switched from low-spin to high-spin after light irradiation at low temperature. This account summarizes the findings in this area of photomagnetism where 57Fe Mössbauer spectroscopy was used as a primary detection tool of the LIESST effect.
Keywords: photomagnetism